Muscle activation patterns in acceleration-based phases during reach-to-grasp movement - Tokuda, Keisuke (J Phys Ther Sci, 2016)
[Purpose] An earlier study divided reaching activity into characteristic phases based on hand velocity profiles. By synchronizing muscle activities and the acceleration profile, a phasing approach for reaching movement, based on hand acceleration profiles, was attempted in order to elucidate the roles of individual muscle activities in the different phases of the acceleration profile in reaching movements. [Subjects and Methods] Ten healthy volunteer subjects participated in this study. The aim was to electromyographically evaluate muscles around the shoulder, the upper trapezius, the anterior deltoid, the biceps brachii, and the triceps brachii, most of which have been used to evaluate arm motion, as well as the acceleration of the upper limb during simple reaching movement in the reach-to-grasp task. [Results] Analysis showed the kinematic trajectories of the acceleration during a simple biphasic profile of the reaching movement could be divided into four phases: increasing acceleration (IA), decreasing acceleration (DA), increasing deceleration (ID), and decreasing deceleration (DD). Muscles around the shoulder showed different activity patterns, which were closely associated with these acceleration phases. [Conclusion] These results suggest the important role of the four phases, derived from the acceleration trajectory, in the elucidation of the muscular mechanisms which regulate and coordinate the muscles around the shoulder in reaching movements.